Cardiovascular problems in emergency medicine a discussion-based review - Grossman, Shamai A.; Rosen, Peter, 1935-; ebrary, Inc. (Chichester, West Sussex : John Wiley & Sons, 2011)
"This is a unique book in emergency medicine providing real discussions on emergency cardiac cases by world famous emergency physicians. Each chapter starts with a case and conversation between the authors on how to diagnose and manage the patient. The case discussion is followed by comprehensive information on diagnosis and management of the condition, providing the wider context, backed up with references, making the book a stand alone text of cardiac emergencies. Authored by experts in the field, this essential guide provides emergency physicians, nurses, EMTs and residents with a handy reference containing recommendations for managing cardiac emergency care. What makes the book unusual is that the chapters are unlike any other EM book written. Essentially this is an opportunity for the reader to learn from the discussions amongst the experts This is the first volume in a projected series Current Topics in Emergency Medicine edited by Peter Rosen and Shamai Grossman. The discussion-based format will be used for each book in the series"--Provided by publisher.
section 1. Cardiac ischemia -- section 2. Cardiac dysrhythmias -- section 3. Non ischemic cardiac disease -- section 4. Vascular emergencies -- section 5. Cardiac testing -- section 6. Cardiac surgery complications.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Cardiovascular emergencies -- Case studies; Evidence-based medicine -- Case studies; Electronic books